The Effect of Financial Inclussion and Social Influence on Community Interest in Using Financial Technology - Yuniarti , Nevita; Safitri, Teti Anggita (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
The development of world technology, especially in Indonesia, is progressing. Many new and innovative creative ideas have emerged in the field of digital technology. Currently, in the financial sector, various technological innovations have emerged that make it easier to carry out financial transactions and other financial activities carried out by the general public, commonly known as FinTech, or Financial Technology. FinTech is a very potential opportunity during COVID-19. However, there are still many people who do not understand the concept of financial inclusion, for example in the use of financial products. The Yogyakarta Financial Inclusion Index is a composite of 76.12%, conventional 75.85%, and Sharia 8.92%. Increasing financial inclusion through fintech cannot be separated from the social influence that accompanies every trend in society in the use of financial services. The type of research used is quantitative. The purpose of this study was to determine whether there is an influence of financial inclusion and social influence on people's interest in using FinTech in the special region of Yogyakarta. primary data source using a primary data questionnaire with 114 respondents and e-wallet users. The results of this study indicate the influence of financial inclusion and social influence on interest in using FinTech. Because of how easy it is for people to get to and use FinTech, like e-wallets, to make transactions easier.